The Influence of Cognitive Behavioral Therapy in Addressing Bullying Behavior among Seventh Grade Students : A Case Study at a Faith-based Private High School, Gowa, Indonesia - Rismayanti; M. Syahri; Tinus, Agus (International Journal of Learning Reformation in Elementary Education, 2025)
This study investigates the effectiveness of Cognitive Behavior Therapy (CBT) in reducing bullying behavior among seventh-grade students at a Faith-based Private High School, Gowa, Indonesia. Utilizing a quantitative associative research design, the study examines the relationship between CBT implementation and changes in students’ behavioral patterns. The sample was selected using purposive sampling techniques, with data collected through validated and reliable questionnaires. The results of the t-test revealed a significant negative effect of CBT on bullying behavior, while the F-test confirmed the overall model's significance. These findings demonstrate that CBT can effectively restructure distorted cognitions and reduce aggressive tendencies in school settings. The intervention not only addresses the cognitive and emotional aspects of bullying but also supports the development of a healthier classroom climate. The study contributes to the growing body of evidence supporting CBT as a practical and impactful approach in school-based mental health and behavioral interventions. Further research is encouraged to evaluate the long-term effects and scalability of CBT within diverse educational contexts.